The Zn-finger of Saccharomyces cerevisiae Rad18 and its adjacent region mediate interaction with Rad5. Issue 4 (11th February 2021) - Frittmann, Orsolya; Gali, Vamsi K; Halmai, Miklos; Toth, Robert; Gyorfy, Zsuzsanna; Balint, Eva; Unk, Ildiko
Abstract: DNA damages that hinder the movement of the replication complex can ultimately lead to cell death. To avoid that, cells possess several DNA damage bypass mechanisms. The Rad18 ubiquitin ligase controls error-free and mutagenic pathways that help the replication complex to bypass DNA lesions by monoubiquitylating PCNA at stalled replication forks. In Saccharomyces cerevisiae, two of the Rad18 governed pathways are activated by monoubiquitylated PCNA and they involve translesion synthesis polymerases, whereas a third pathway needs subsequent polyubiquitylation of the same PCNA residue by another ubiquitin ligase the Rad5 protein, and it employs template switching. The goal of this study was to dissect the regulatory role of the multidomain Rad18 in DNA damage bypass using a structure-function based approach. Investigating deletion and point mutant RAD18 variants in yeast genetic and yeast two-hybrid assays we show that the Zn-finger of Rad18 mediates its interaction with Rad5, and the N-terminal adjacent region is also necessary for Rad5 binding. Moreover, results of the yeast two-hybrid and in vivo ubiquitylation experiments raise the possibility that direct interaction between Rad18 and Rad5 might not be necessary for the function of the Rad5 dependent pathway. The presented data also reveal that yeast Rad18 uses different domains to mediate its association with itself and with Rad5. Our results contribute to better understanding of the complex machinery of DNA damage bypass pathways.